Analysis of the readiness for healthcare personnel adopting telerehabilitation: An interpretive structural modelling (ISM) approach - Bahari M.; Jafni T.I.; Ismail W.; Hashim H.; Hussain H. (Springer Verlag, 2024)
Indexed by Scopus